Nomogram prediction for periodontitis in Chinese pregnant women with different sociodemographic and oral health behavior characteristics: a community-based study - Qiao Shi; Yu Cai; Xiaoxuan Wang; Guojing Liu; Qingxian Luan (BMC, 2024)
Abstract Background Periodontitis is associated with poor pregnancy outcomes, indicating periodontal health as an important health concern for pregnant women. Herein, this study identified risk indicators for periodontitis and developed a nomogram for predicting the risk of periodontitis in pregnancy by analyzing periodontitis and associated factors in pregnant women. Materials and methods A community-based cross-sectional study was conducted by including 438 pregnant women at 10-36 gestational weeks from Langfang, China. Pregnant women were examined for periodontal status, and their demographic, socioeconomic, and oral health behavior data were collected. Potential influencing factors of periodontitis were analyzed with univariate and multivariate logistic regression analyses. A nomogram was developed, followed by the assessment of its validation and discriminatory abilities. Results The prevalence of periodontitis was 59.8% in pregnant women. Periodontitis-associated variables in pregnant women were gestational age, non-first pregnancy, daily tooth brushing frequency of ≤ 1 before pregnancy, and annual frequency of periodontal treatment < 1 (including no periodontal treatment). The risk of periodontitis was positively associated with gestational age (OR = 1.28, 95% CI = 1.17-1.39, p < 0.001). Pregnancy history showed a strong positive association (OR = 6.57, 95% CI = 1.22-35.43, p = 0.03). Daily tooth brushing frequency before pregnancy was also positively associated with periodontitis (OR = 1.54, 95% CI = 1.03-2.79, p = 0.05). Additionally, the annual frequency of periodontal treatment exhibited a positive association, with higher odds observed for those with less frequent treatment (OR = 2.28, 95% CI = 1.25-4.14, p = 0.05; OR = 7.37, 95% CI = 3.04-22.06, p < 0.001). These four factors were used to develop a nomogram for predicting periodontitis in pregnant women. The area under the receiver operating characteristic curve of the nomogram was 0.855 and 0.831 in the training and testing cohorts, respectively, reflecting the superior prediction accuracy of the nomogram. The calibration curve and decision curve analysis demonstrated the good performance and net benefit of the nomogram. Conclusion Risk factors for periodontitis in pregnant Chinese women include gestational age, non-first pregnancy, lower frequency of daily tooth brushing before pregnancy, and lower frequency of periodontal treatment. An easy-to-use nomogram with acceptable accuracy can allow for the prediction of periodontitis risk in pregnant Chinese women. Clinical relevance With the assistance of this nomogram, clinicians can evaluate the risk of periodontitis in pregnancy, thereby offering more tailored oral health education to women of reproductive age.